2019
DOI: 10.1177/0890117119854708
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Supplemental Nutrition Assistance Program Use at Farmers’ Markets With Monetary Incentive Programming

Abstract: Purpose: Healthy food incentive program implementation targeting people receiving Supplemental Nutrition Assistance Program (SNAP) benefits is supported by the federal Food Insecurity Nutrition Incentive (FINI) grant program. This study examined factors contributing to increased SNAP use at farmers’ markets with an FINI-funded incentive program. Design: Implementation evaluation. Setting: Sixteen states and District of Columbia. Participants: Two hundred eighty-two FINI-funded farmers’ markets open in 2016. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The NI literature review revealed variation in the strength of evidence for pathways. For example, evidence describing what participants need to successfully use NIs was well-developed [ 18 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. However, there was no evidence describing how projects can support participation by farmers.…”
Section: Resultsmentioning
confidence: 99%
“…The NI literature review revealed variation in the strength of evidence for pathways. For example, evidence describing what participants need to successfully use NIs was well-developed [ 18 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. However, there was no evidence describing how projects can support participation by farmers.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond generating revenues for local farmers, benefits include the development of the local agri-food system, revenue for surrounding businesses, and opportunities for local entrepreneurs [52][53][54][55][56][57][58][59]. Economic benefits also extend to consumers through enhanced access to affordable food [60][61][62][63][64]. Studies identified "measurable improvements in economic access to and increased consumption of fresh produce" [51] (p. 6), especially in underserved communities.…”
Section: The Potential Benefits and Risks Associated With Farmers Mar...mentioning
confidence: 99%
“…In particular, the amount of FVs purchased and SNAP utilization associated with financial incentives have a substantial impact on local food economies via an influx of funds into the community supporting local farmers and retailers [ [22] , [23] , [24] , [25] ]. Some studies also demonstrate an increase in SNAP sales at farm-direct settings with the addition of NI programs, fueling economic growth in the local agriculture sector, benefiting both the participants with low income and the local farmers, some of whom may also receive federal food assistance [ [26] , [27] , [28] , [29] , [30] ].…”
Section: Introductionmentioning
confidence: 99%